ANALISIS DAN KOORDINASI SIMPANG KARTINI DAN SIMPANG SIDODADI, SEMARANG - Ainul Misbahul Munir; Fariz Hadiyanto; Bambang Riyanto; Epf. Eko Yulipriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Volume growth in road traffic is increasing rapidly, especially in the city of Semarang. This makes the occurrence of congestion in the city of Semarang at peak hours, especially at intersections. The problems at the intersection can be overcome by the use of lights at signalized intersections so there is no conflict and clash, but the use of a signal at the intersection also raises its own problems, such as delays and queues occur, especially if there are a lot of adjacent signalized intersections in the road as well as on the road Dr.Cipto Mangunkusumo Semarang who are familiar with the way Dr.Cipto. This study aims to smooth traffic flow on roads Dr.Cipto coordinated way Kartini intersection and Sidodadi intersection. The data was collected by surveying directly at the two junctions at peak hours in the morning, afternoon, and evening. The data is taken from the volume of vehicles that pass through each intersection, signal timing, vehicle travel speed through two intersections, queue length, and geometric intersection. The survey results are then processed using the guidelines Indonesian Highway Capacity Manual (MKJI) in 1997 to obtain the performance of the existing condition, then performed traffic control and compared the results of its performance in optimal condition and scenario conditions. Best performance at each intersection are then used to create a draft of coordination between the two junctions. Results in the condition of existing intersection analysis showed unsatisfactory performance, at the intersection of Kartini shows the degree of saturation is still high in some approach, a large value of the vehicle stop, and delay simpangnya was still great. In planning the optimal conditions has a better performance than optimal conditions seen from the DS and the average intersection delay is smaller than the existing condition, while the condition of scenario planning produces a worse performance than the optimal conditions, so the recommended optimal conditions for used in coordination signalized intersections Kartini and Sidodadi. To perform coordination between the two signalized intersections, planning done is create two junctions cycle time has the same value, the morning peak hour cycle time changed to 82 seconds, the peak daylight hours to 75 seconds, and afternoon peak hours to 100 seconds. Of the distance between the intersection and the vehicle speed obtained offset value is 36 seconds while the bandwidth at peak hours in the morning for 25 seconds, 22 seconds during peak hours, and the afternoon peak hour by 32 seconds. While the efficiency of the coordination of the two junctions of 30.48% for the morning, 29.33% for the day, and 32% for the afternoon. Estimated at morning peak hour north approach can release 2238 vehicles/hour, the afternoon peak hour of 2160 vehicles/hour, and the afternoon peak hour of 2376 vehicles/hour. Coordination performance was good enough for the level of short-term treatment. Thus, it can be concluded that the performance of intersections to be better in terms of the initial conditions.